Dandelion fire [compact disc, unabridged] - Wilson, Nathan D. (Wilson, Nathan D. 100 cupboards (Listening Library), 2009)
Presents the continuing adventures of Henry York, who has been living in Kansas with his cousins, where he discovers doorways leading to other worlds and becomes involved in a multi-world struggle between good and evil.